Low expression of estrogen receptor β in T lymphocytes and high serum levels of anti-estrogen receptor α antibodies impact disease activity in female patients with systemic lupus erythematosus. Issue 1 (December 2016) - Maselli, Angela; Conti, Fabrizio; Alessandri, Cristiano; Colasanti, Tania; Barbati, Cristiana; Vomero, Marta; Ciarlo, Laura; Patrizio, Mario; Spinelli, Francesca; Ortona, Elena; Valesini, Guido; Pierdominici, Marina
Abstract Background Current evidence indicates that estrogens, in particular 17β-estradiol (E2), play a crucial role in the gender bias of autoimmune diseases although the underlying molecular mechanisms have not yet been fully elucidated. Immune cells have estrogen receptors (ERs), i.e., ERα and ERβ, that play pro- and anti-inflammatory functions, respectively, and the presence of one estrogen receptor (ER) subtype over the other might change estrogen effects, promoting or dampening inflammation. In this study, we contributed to define the influences of E2 on T cells from female patients with systemic lupus erythematosus (SLE), a representative autoimmune disease characterized by a higher prevalence in women than in men (female/male ratio 9:1). Particularly, our aim was to evaluate whether alterations of ERα and ERβ expression in T cells from female SLE patients may impact lymphocyte sensitivity to E2 and anti-ERα antibody (anti-ERα Ab) stimulation interfering with cell signaling and display a direct clinical effect. Methods Sixty-one premenopausal female patients with SLE and 40 age-matched healthy donors were recruited. Patients were divided into two groups based on the SLE Disease Activity Index 2000 (SLEDAI-2K) (i.e., <6 and ≥6). ER expression was evaluated in T lymphocytes by flow cytometry, immunofluorescence, and Western blot analyses. Serum anti-ERα Ab levels were analyzed by enzyme-linked immunosorbent assay (ELISA). ER-dependent signaling pathways were measured by a phosphoprotein detection kit. Results Intracellular ERβ expression was significantly lower in T cells from patients with SLEDAI-2K ≥6 as compared with healthy donors and patients with SLEDAI-2K <6 and negatively correlated with disease activity. The expression of intracellular and membrane-associated-ERα was similar in SLE and control T cells. ER-dependent signaling pathways were activated in T cells from SLE patients with SLEDAI-2K ≥6, but not with SLEDAI-2K <6, when both membrane and intracellular ERs were stimulated by co-treatment with E2 and anti-ERα Abs. Conclusions Our results demonstrate an altered ER profile in SLE patients, possibly contributing to SLE pathogenesis and interfering with clinical activity, and highlight the potential exploitation of T cell-associated ERβ as a biomarker of disease activity.